2017
DOI: 10.1159/000477179
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Sign: A Poor Outcome Predictor in Intracerebral Hemorrhage

Abstract: Background: The presence of high-density starry dots around the intracerebral hemorrhage (ICH), which we termed as a satellite sign, is occasionally observed in CT. The relationship between ICH with a satellite sign and its functional outcome has not been identified. This study aimed to determine whether the presence of a satellite sign could be an independent prognostic factor for patients with ICH. Methods: Patients with acute spontaneous ICH were retrospectively identified and their initial CT scans were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 29 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…Island sign was referred to ≥3 scattered small hematomas, with complete hematoma separation; ≥4 scattered small hematomas partly or all connected with the main hematoma; round or oval scattered small hematomas separated from the main hematoma; foam or bud small hematomas connected with the main hematoma [10]. Satellite sign was at least one small hematoma separated from the main hematoma; the maximum transverse diameter of the small hematoma was <10 mm; the minimum distance between the small hematoma and the main hematoma was between 1 and 20 mm; subarachnoid hemorrhage and intraventricular hemorrhage were not included [11].…”
Section: Imaging Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Island sign was referred to ≥3 scattered small hematomas, with complete hematoma separation; ≥4 scattered small hematomas partly or all connected with the main hematoma; round or oval scattered small hematomas separated from the main hematoma; foam or bud small hematomas connected with the main hematoma [10]. Satellite sign was at least one small hematoma separated from the main hematoma; the maximum transverse diameter of the small hematoma was <10 mm; the minimum distance between the small hematoma and the main hematoma was between 1 and 20 mm; subarachnoid hemorrhage and intraventricular hemorrhage were not included [11].…”
Section: Imaging Data and Analysismentioning
confidence: 99%
“…Non-contrast CT is the first choice of conventional examination in ICH because of its fastness and convenience. Recently, non-contrast CT markers, including hypodensities [6], hematoma density [7], blend sign [8], black hole sign [9], island sign [10], and satellite sign [11], are reported to be related with poor outcome in ICH. Therefore, we aim to develop a predictive model based on these markers in an ICH cohort and validate it in another cohort.…”
Section: Introductionmentioning
confidence: 99%
“…However, CTA is not routinely used in many institutions (18). Recently, several NCCT markers have shown the ability to predict HE (19), such as the blend sign (BS) (20), black hole sign (BHS) (21), satellite sign (22), and island sign (23). Which imaging marker is better at predicting the EHE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some biochemical parameters, such as cholesterol and ferritin level, were also reported to be biomarkers of outcomes [ 10 , 11 ]. Besides, it has been suggested that brain imaging parameters may predict outcome in ICH patients, for example, satellite sign and blend sign in the initial CT scan [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%